Accuracy of Injury Severity Ratings on Police Crash Reports. Issue 1 (January 2015) - Burdett, Beau; Li, Zhixia; Bill, Andrea R.; Noyce, David A.
Injury severity as assessed by law enforcement officers on crash reports, particularly incapacitating injuries (severity = A on the KABCO scale, on which K denotes a fatal injury, A an incapacitating injury, B a non-incapacitating injury, C a possible injury, and O a property-damage-only crash, is used for estimating crash costs and, in turn, for allocating safety funds. The Crash Outcome Data Evaluation System (CODES) database reports injury severity assessment from both law enforcement officers using the KABCO scale and medical practitioners using the Maximum Abbreviated Injury Score (MAIS). The objective of this study was to analyze the accuracy of the injury severity ratings on Wisconsin crash reports by comparing crash data in the CODES database between 2008 and 2012. Results indicated that 66.6% of KABCO A crashes had only minor or moderate injury severities (MAIS 1 or 2); that is, two-thirds of crash victims' injury severities were overestimated. In addition, underestimation of injury severities occurred in 2.9% of all O, C, and B crashes. Further analyses found that injuries to all body regions statistically contributed to overestimation and underestimation as compared with injuries to body regions from all crash reports, with the exception of lower extremities for underestimated crashes. Several factors including gender, vehicle type, and the presence of alcohol significantly contributed to both overestimation and underestimation. Lighting conditions also affected underestimation. Spine, thorax, and abdomen or pelvic injuries were the injuries most frequently missed by law enforcement officers. The most common injuries found in the inaccurate crash reports were bone injuries, lacerations, abrasions, and contusions. These findings were used to develop guidance for law enforcement officers to assist in more accurate injury severity assessments.